Respectful maternity care and associated factors among mothers who gave birth at public health institutions in Debre Tabor town, Northwest Ethiopia: a mixed-methods study - Fentie, Tadesse Ayana; Solomon, Abayneh Aklilu; Enyew, Mihretu Molla; Beyene, Meseret Mekuriaw; Melese, Ayalew Kassie; Belay, Alamirew Enyew; Alemu, Gebrie Getu (Frontiers in Global Women's Health, 2025)
BackgroundRespectful maternity care is care organized for and provided to all women in a manner that maintains their dignity, privacy, and confidentiality, ensures freedom from harm and mistreatment, and enables informed choice and continuous support during labor and childbirth. However, in many healthcare settings in Ethiopia, the standard practice of respectful obstetric care is not the norm, and a significant proportion of health professionals view patients merely as cases and do not show compassion.ObjectivesTo assess respectful maternity care and associated factors among mothers who gave birth at public health institutions in Debre Tabor town, Northwest Ethiopia from December 1, 2023, to January 30, 2024.MethodsAn institution-based cross-sectional study was conducted using qualitative and quantitative data collection methods. Three hundred seventy participants were selected for quantitative analysis using systematic random sampling, while eight were chosen for the qualitative study through purposive sampling. The quantitative data were coded and entered into Epi Data version 4.6, then exported to the Statistical Package for the Social Sciences (SPSS) version 25 for analysis. A multivariable logistic regression analysis was performed to identify factors associated with the outcome variable. Adjusted odds ratios with 95% confidence intervals were computed to determine the significance level. Thematic analysis was used for the qualitative data.ResultsThe proportion of respectful maternity care was 34.1% (95%CI: 29.4, 39.2) cesarean delivery [AOR = 3.45, 95%CI: 1.60, 7.42]. Daytime delivery [AOR = 3.14, 95%CI: (1.59, 6.18)] and less than or equal to 1 day stay in a healthcare facility [AOR = 3.03, 95%CI: (1.51, 6.08)] were positively associated with respectful maternity care. Inadequate equipment and supplies, shortage of staffing, and lack of accountability were barriers to providing respectful maternity care.ConclusionsThe proportion of respectful maternity care was low. Therefore, health institutions and other stakeholders should support and strengthen monitoring and evaluation mechanisms for maternal and neonatal healthcare providers and enhance education and constant support for women during their pregnancy and childbirth. Additionally, adequate access to basic equipment and supplies should be given due attention to ensure respectful maternity care.